ANTESEDEN DAN KONSEKUENSI BRAND LOYALTY PADA KONSER FESTIVAL MUSIK THE SOUND PROJECT - Hasna Aprilia; Robert Kristaung (Politeknik Bisnis Indonesia, 2023)
This study aims to analyze the relationship between social media marketing efforts and customer brand engagement in driving the willingness to pay a premium price at The Sound Project music festival concerts. In today's digital era, social media has become an effective platform for promoting products and establishing customer relationships. Customer brand engagement is a crucial factor in influencing the willingness to pay a premium price, which serves as an indicator of long-term business success. This research employs a quantitative method by collecting data through questionnaires distributed to attendees of The Sound Project music festival concerts. Data analysis is conducted using multiple linear regression techniques to examine the relationship between social media marketing variables and customer brand engagement in influencing the willingness to pay a premium price. The findings of this study are expected to provide a better understanding of the importance of social media marketing efforts in creating customer brand engagement and enhancing the willingness to pay a premium price within the Indonesian music industry. The practical implications of this research emphasize the significance for The Sound Project managers to optimize social media usage in their marketing strategies to build strong customer brand engagement and enhance the willingness to pay a premium price.